ANALISIS RASIO LIKUIDITAS, RASIO PROFITABILITAS DAN SALES GROWTH PRA DAN PASCA BERLAKUNYA UNDANG-UNDANG BADAN PENYELENGGARA JAMINAN SOSIAL - Stevany Febreany, SE., M.Ak. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
The National Health Insurance Program is a compulsory social health insurance. This social security has good and bad effects. Its good effect is the community gets social protection in the form of health facilities. But it is estimated the adverse effects experienced by pharmaceutical companies. The price of the product in the era of the National Health Insurance has been determined by the government, where the price is below the company's production costs coupled with the deficit experienced by the Social Security Organizing Agency (BPJS) resulting in the company having to operate on a low profit and low margin basis. The purpose of this study is to identify financial conditions in the pre and post National Health Insurance era. The research method used is quantitative descriptive research method with financial ratio comparison analysis tools, namely liquidity ratios calculated through cash ratios, profitability ratios calculated through net profit margins and sales growth in the financial statements of PT Hexpharm Jaya Laboratories from 2009-2013 and 2014- 2018. The results showed that the liquidity ratio calculated by cash ratio and profitability ratio calculated with net profit margin was lower when the National Health Insurance was lower than the National Health Insurance. Sales growth experienced growth after the National Health Insurance.